Estudo fitossanitário, multiplicação e taxonomia de nematoides encontrados em sementes de gramíneas forrageiras no Brasil - Favoreto, Luciany; Santos, Jaime M.; Calzavara, Sérgio Ademir [UNESP]; Lara, Luciano A. (My University, 2011)
Pathogens in seeds imply quarantine constraints for exportation. This research aimed to quantify nematodes and fungus populations in seed samples of forage grasses from the main Brazilian producing states, and to multiply the nematodes in vitro, as well to study the taxonomy of the nematodes detected. Seed samples of 237 lots of different forage grasses from São Paulo, Minas Gerais, Mato Grosso do Sul, Mato Grosso, Bahia, and Goias States were collected and shipped for analyses in the Nematology and Plant Pathology Laboratories at FCAV[long dash]UNESP [long dash] Jaboticabal( SP) by Comercio e Industria Matsuda Imp., Exp. Ltd. Nematodes were extracted from 10 g of seeds. To detect the fungus, the Blotter-test was applied. The identifications were done by using a photonic microscope and a stereomicroscope. For the study of in vitro multiplication of the nematodes, the following parthenogenetic species were selected: Aphelenchoides sexlineatus, Aphelenchus sp. and Ditylenchus montanus. Cultures of the fungi Fusarium sp. and Didymella brioniae were used as substrate to multiply the nematodes in Petri dishes. Each plate was inoculated with 10 mature females, then incubated in B.O.D. at 25 [plus or minus]1 [degree]C, in the dark. Thirty days after inoculation, the nematodes were extracted. The populations obtained in the suspensions were estimated in the microscope using Peters counting chamber, and the reproduction factor estimated. For the taxonomic study of the nematodes, morphological characters of specimens were recorded under the light and scanning electron microscopes. The results indicated a large distribution of nematodes and fungus in seeds of forage grasses in Brazil. The nematodes identified in the present study were: Aphelenchoides besseyi, A. bicaudatus, A. fragariae, A. sexlineatus, Ditylenchus myceliophagus, D. dipsaci, D. montanus, and Aphelenchus sp. In addition, species of the fungi Fusarium, Helminthosporium and Phoma were recovered.
Phytosanitary study, multiplication and taxonomy of nematodes associated with seeds of forage grasses in Brazil.